Change toward healthier lifestyles is associated with better health-related quality of life in long-term colorectal cancer survivors - Eyl-Armbruster, Ruth Elisa; Thong, Melissa S. Y.; Carr, Prudence R.; Jansen, Lina; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann; Arndt, Volker (Journal of the National Comprehensive Cancer Network, 2022)
Background: Little is known about how changes in a constellation of lifestyle factors affect health-related quality of life (HRQoL) in colorectal cancer (CRC) survivors. Our study aimed to investigate the association between changes in healthy lifestyle and HRQoL over time in survivors of stage I-IV CRC. Methods: We included 2,283 long-term